Does Legalization of Sunday Alcohol Sales Increase Crime? - Jungtaek Lee; Baris K. Yörük (Center for Economic Studies and ifo Institute (CESifo), 2014)
Recently, several states repealed their laws restricting the sale of alcohol on Sundays. We investigate the effect of this policy change on crime trends in seven states using data from FBI's National Incident-Based Reporting System (NIBRS). We identify the impact of the legalization of Sunday alcohol sales on several different types of criminal activity by exploiting the variation in the implementation of this policy change across different states at different times. Using difference-indifferences type models, we show that the repeal of the ban on Sunday alcohol sales is associated with significant increases in total property and violent crimes committed on Sundays. In particular, we find that states that legalized Sunday sales of alcohol experienced 13% to 20% increase in the total number of violent and property crimes committed on Sundays. However, the aggregate impact of this policy change on crimes committed on all days of the week is not significant due to either positive or statistically insignificant spillover effects of the repeal of Sunday alcohol sales bans on crimes committed on Mondays through Saturdays. These results are robust under alternative model specifications and several falsification tests.
Keywords: I18; K42; 330; Sunday alcohol sales; alcohol consumption; criminal activity